Implementasi Contextual Teaching and Learning (CTL) dalam Kurikulum Berbasis Kompetensi Mata Pelajaran Geografi SMU/MA - Mochamad Enoh (Universitas Negeri Malang, 2016)
The competence-based curriculum (CBC) must be followed-up by developing its syllabi. CBC allows the regions or schools to develop their own syllabi that refer to the basic competence set by the curriculum center. There by the syllabi will be more relevant to the condition and the interest of the regional stakeholders. The teaching method should be contextual. This article, concerns a critical analysis of how the learning experience and the teaching materials of Geography subject are designed based on CTL. The students must have contacts with the real world.